Reel partnerships: Six directors and their proteges tell their tales in Astro's new initiative, Karya 12. - Yeoh, Angelin (The Star, 2016)
What if the skin used for wayang kulit puppets are made from human instead of the usual buffalo or goat hide? That is the premise for director Micheal Ang's upcoming telemovie Kulit.